Vanished [compact disc, unabridged] - Finder, Joseph (Macmillan Audio, 2009)
Special Forces turned investigator Nick Heller has exposed some the world's most powerful men, making several enemies along the way. However, nothing has prepared him after receiving a panicked phone call from his nephew, who relays that Nick's mother has been attacked and lies in a coma. In an attempt to discover the identity of his mother's attacker, Nick seeks out his brother, Roger, who has established himself as one of the country's foremost gangsters.